'The sheer number of Russians is smothering us' a Colonel-General Erich Hoepner's Private Letters on the Road to Moscow (October 1941 – January 1942). Issue 2 (3rd April 2022) - Stahel, David
ABSTRACT: The German campaign against the Soviet Union is typically reconstructed from military files that offer a largely dispassionate view, recording events rather than opinions. Gaining insights into the minds of key German commanders is much more difficult and often a matter of speculation, which all too often reflect the supposition of the author rather than anything concrete about the protagonist. Yet almost every German general wrote letters home to their wives and families in which – from the surviving examples – they offered surprising frank commentaries on the conduct of their operations. One such insightful collection is by Colonel-General Erich Hoepner, the commander of Panzer Group 4 in 1941.